ANALISIS YURIDIS PENEGAKAN HUKUM TINDAK PIDANA KORUPSI DALAM PENJATUHAN VONIS HAKIM - Utami, Rizky Dwi; Saputra, M Adi (Bahasa Indonesia, 2024)
The judge's consideration is one of the most important points in realizing the value of a judge's decision which contains justice (ex aequo et bono) and contains legal certainty, of course it is also beneficial for the parties concerned. However, sometimes it is felt that the judge's decision in corruption decisions has not touched the legal objective. Therefore, the author wants to know about law enforcement in the consideration of judges in imposing a decision (Decision Study Number: 01/Pid.Sus.TPK/2017/PN.Mdn). The writing of this research uses the normative juridical research method, which is a method used to review/analyze data in the form of legal materials, especially primary legal materials and secondary legal materials related to the material discussed. Based on the results of the analysis, it can be concluded that the basic considerations of judges in imposing a decision are based on juridical considerations and non-juridical considerations. Where this is the District Court in determining judex facti, with the authority to examine the facts and evidence of a case. While the factors of law enforcement of corruption in the imposition of judges' verdicts (Decision Study Number: 01/Pid.Sus.TPK/2017/PN.Mdn) can be determined from 5 factors namely, Legal Factors, Law Enforcement Factors, Facilities and Infrastructure Factors, Community Factors and Cultural Factors. Where from the judge's verdict can analyze law enforcement.